BENEFITS OF USING VIDEO IN ELT (American Journal of Research in Humanities and Social Sciences, 2022)
This article discusses the effectiveness of using video in English Language Teaching. Several works of scientists on this subject have been investigated. Different views of the technique (by scientists) were shown as examples. The researcher investigates the implementation of video in teaching English language by a few methods. Besides that, author tries to show the usage of it in the classroom, as well as, advantages and disadvantages of the technology.